2000
DOI: 10.1046/j.1365-2141.2000.02047.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and insulin‐like growth factor I support the proliferation of erythroid progenitor cells in bone marrow through the sharing of receptors

Abstract: Summary. The effects of insulin and insulin-like growth factor I (IGF-I) on the proliferation of erythroid progenitor cells in bone marrow were studied in serum-deprived culture. Primitive human bone marrow cells were purified by cell sorting on the basis of the expression of CD34 and the Kit receptor. Insulin and IGF-I with erythropoietin (EPO) dose dependently supported the formation of erythroid colonies of CD34 1 /Kit 1 cells in bone marrow. The direct effect of insulin and IGF-I on the stimulation of prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 44 publications
(59 reference statements)
4
62
0
1
Order By: Relevance
“…It is beyond the scope of this pilot study to elucidate the molecular mechanisms by which insulin interacts with PC mobilization. However, influences of insulin on chemotaxis and inflammatory reactions (16 -18), as well as proliferation of PCs (19), should be considered, and ongoing studies should aim to answer some of the questions addressed. This pilot study is not sufficient to rule out minor effects of hyperglycemia and oxidative stress on PC mobilization and demands for larger clinical trials to study the effects of different insulin preparations (insulin analogs) on PC mobilization and development of diabetes complications.…”
Section: Results -Numbers Of Circulating Cd34mentioning
confidence: 99%
“…It is beyond the scope of this pilot study to elucidate the molecular mechanisms by which insulin interacts with PC mobilization. However, influences of insulin on chemotaxis and inflammatory reactions (16 -18), as well as proliferation of PCs (19), should be considered, and ongoing studies should aim to answer some of the questions addressed. This pilot study is not sufficient to rule out minor effects of hyperglycemia and oxidative stress on PC mobilization and demands for larger clinical trials to study the effects of different insulin preparations (insulin analogs) on PC mobilization and development of diabetes complications.…”
Section: Results -Numbers Of Circulating Cd34mentioning
confidence: 99%
“…These reports raise the possibility that insulin deficiency may increase GA formation through the down-regulation of albumin synthesis and prolongation of the half-life of this protein, while insulin resistance and compensatory hyperinsulinemia may decrease GA formation through the upregulation of albumin metabolism. Regarding the RBC lifespan, insulin may also influence erythropoiesis [11], while an increase of Hb and the RBC count has been observed in subjects with the insulin resistance syndrome [12] or metabolic syndrome [13]. Although these reports suggest that GA and HbA1c may be affected by plasma insulin level and insulin resistance through influences on albumin metabolism or erythropoiesis, direct information about whether these factors actually modify the formation of GA or HbA1c in diabetic patients has not been obtained.…”
Section: Discussionmentioning
confidence: 99%
“…However, understanding the mechanisms that direct myeloid-cell development and differentiation might require further events linking external stimuli and geneexpression cascades. As an example, in the erythroid-cell lineage (a subclass of the myeloid lineages), in addition to the well-established role of both the erythropoietin/erythropoietinreceptor (Epo/Epo-R) pair and the GATA1 transcription factor, other extrinsic signaling molecules including Wnt/frizzled (Van Den Berg et al, 1998), TGFβ (Zermati et al, 2000), fibroblast growth factors (Huber et al, 1998), growth-factorindependence 1B (Osawa et al, 2002), insulin and insulin-like growth factor (Miyagawa et al, 2000), and intrinsically acting factors such as caspases (Zermati et al, 2001) have been reported to be important for erythropoiesis. Further identification of either novel molecules or complex sets of interactions between already-identified crucial transcription factors and co-factors might help to elucidate the molecular mechanisms that control the myeloid differentiation process.…”
Section: Introductionmentioning
confidence: 99%